Application of Enzyme Immobilization Technology in Hydrolytic Enzyme Sludge Reduction System - Li Jia; Min Sun (Chemical Engineering Transactions, 2017)
The excess sludge has become one of the most serious burdens of urban sewage treatment plants, because of their huge production, high processing costs and the serious pollution to the ambient environment. In this work, aiming to reduce the production of excess sludge, we choose the hydrolases, which have excellent catalytic hydrolysis and can efficiently hydrolyze bacterial cells, to analyze the sludge from the activated sludge system during the operational process. This research can broaden the sludge reduction field, deepen the mechanism of the reduction technology, and develop a reliable method to apply in the sludge reduction engineering. First, the effects of several typical hydrolases on lysing the sludge from the activated sludge system were analyzed, whose results showed that compared to a-amylase and protease, lysozyme is the most effective for the hydrolysis of the sludge with the same dosage of enzyme. Subsequently, the selected lysozyme was added in the sludge from the SBR system by static test reactor. And the most suitable hydrolysis conditions were obtained at the 0.072-0.250 g lysozyme /g MLSS, 30-60min, 30-40 ◦C.